Valuing Time-Varying Attributes Using the Hedonic Model: When Is a Dynamic Approach Necessary? - Bishop, Kelly C.; Murphy, Alvin D. (The Review of Economics and Statistics, 2019)
Abstract We build on the intuitive (static) modeling framework of Rosen (1974) and specify a simple, forward-looking model of location choice. We use this model, along with a series of graphs, to describe the potential biases associated with the static model and relate these biases to the time series of the amenity of interest. We then derive an adjustment factor that allows the potentially biased static estimates to be converted into forwardlooking estimates. Finally, we illustrate these concepts with two empirical applications: the marginal willingness to pay to avoid violent crime and the marginal willingness to pay to avoid air pollution.